Paciente femenino de 40 años de edad con diabetes mellitus tipo 2 y sobrepeso - Olvera Mosquera, Stefanny Andreina (2020)
The present clinical case is about a 40year-old adult woman, is an engineer, married, has 3 children and lives in Babahoyo, with a recent diagnosis of type 2 diabetes mellitus, is being treated with oral metformin 1gr daily, takes medicine , as indicated by the doctor, allergies and surgical history does not refer, within the family pathological history Mother with a diagnosis of Type 2 Diabetes Mellitus, goes to control, does not refer novelty, but indicates that she does not follow the diet or diet recommendations physical activity. To the physical examination, Head and neck without novelty; thorax, auscultation ventilated lung fields, rhythmic heart sounds, depressible abdomen, limbs without novelty.; The nutritional assessment is carried out and its BMI reflects overweight with increased cardiovascular risks; The biochemical nutritional assessment is performed and its results revealed hyperglycemia, high glycosylated hemoglobin, hypercholesterolemia, low hypertriglyceridemia, low HDL and increased LDL, the doctor Considering that the patient does not meet the therapeutic objective (glycosylated hemoglobin less than 7%) before adding another drug, decides to guide the patient to comply with the non-pharmacological treatment, which will help her better metabolic control, so she insists on the importance of diet and physical activity and sends her to the nutrition service for her intervention . An individualized nutritional plan is made to the patient, taking into account their nutritional diagnosis and their pathological condition, a therapeutic dietary plan that meets the daily caloric requirements, the type of diet will be diabetic diet that will be divided into 5 meals a day, in order to maintain optimal metabolic control and avoid other complications. A patient follow-up and monitoring plan is executed in 6 weeks, in which a minimal but continuous weight loss was observed, and its biochemical values varied in a positive way to improve the patient's health condition.